KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MEMECAHKAN MASALAH ALJABAR BERDASARKAN GAYA KOGNITIF FIELD INDEPENDENT - Tanti Erviana (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2019)
This research aims to describe the level of mathematical reasoning ability of students with field-independent cognitive styles in solving algebra problems. The research method used is a qualitative descriptive approach, using qualitative data then described to produce a clear and detailed picture of students' mathematical reasoning with independent field cognitive style in solving algebra problems. The subjects of the research were Class VIII students’ of SMP Negeri 47 Surabaya. The main Instrument in this study is the researchers themselves. Instrument supporters in this research is divided into 2 kinds of Tests, namely the task of problem solving algebra, and guidelines for the interview. Data collection Techniques in the study carried out using two techniques, namely written tests and interviews. The process of data analysis in this study refers to qualitative data analysis process, namely the reduction of data, presenting the data, and draw conclusions. the results of this research indicate that (1) able to conduct an investigation of the problems faced thoroughly, (2) able to plan problem solving by connecting various related information, (3) able to use the strategy chosen correctly and correctly, and (4) able to re-examine, evaluate, and draw valid conclusions based on the solution of the problem obtained. In addition, the results of this study indicate that the level of mathematical reasoning ability of students is in the category sufficient to meet the mathematical reasoning indicators of field-independent cognitive style.